Strategi Manajemen Perubahan Menuju Sekolah Digital: Studi Kasus Program Sempada Berdasi SMP Negeri 2 Pamekasan - Imdadur Rohman; Fina Tamara El-Haris; Zeinal Abidin (re-JIEM (Research Journal of Islamic Education Management), 2026)
This research is motivated by the demands of digital transformation in junior high school learning that still occurs inequity in planning and structured change management by teachers. This study aims to analyze change management strategies towards digital schools: a case study of the SEMPADA BERDASI program at SMP Negeri 2 Pamekasan. This study uses a qualitative approach with a case study research design. Data were collected through in-depth interviews, digital platform observations, and documentation, then a descriptive qualitative analysis was conducted with a case study design. The results show that SMPN 2 Pamekasan has implemented a good change management strategy in conventional schools into a digital school innovation, this program is a digital platform that continues to operate along with the development of the technological era, but currently has not integrated other digital innovation media. The decline in learning enthusiasm and moral quality, has become a stakeholder innovation to create innovations regarding digital schools. Students are captivated by the convenience of the digital era, making it easier for teachers to apply these learning media. Overall, this study confirms the need for strengthening school policies, strategic planning, human resource management, and the organization of those tasked with operating digital platforms. If all these are met properly, the SEMPADA BERDASI program will be more effective and sustainable with increasingly sophisticated innovations in junior high schools.